2019
DOI: 10.18621/eurj.443557
|View full text |Cite
|
Sign up to set email alerts
|

Thiol/disulphide homeostasis in Helicobacter pylori infected patients

Abstract: Objectives:The aim of the study was to evaluate the oxidative stress level in patients, diagnosed with H. pylori infection, using a novel marker (thiol/disulphide homeostasis) and to compare the level in infected individuals with that in healthy volunteers. Methods: A total of 60 patients diagnosed with gastritis, erosive gastritis or ulcer by endoscopy were included and biopsied. The 30 patients diagnosed with H. pylori and 30 healthy individuals were enrolled. Medical histories, physical examination results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Naja et al has found no significant difference in the plasma thiol level in HP infected patients compared with controls [23]. Baykan et al reported that there was no difference between the total thiol, native thiol, disulphide/native thiol and dissulphide/total thiol ratios of the HP (+) patients and control group [24]. They claimed severity of inflammation affected their results.…”
Section: Discussionmentioning
confidence: 96%
“…Naja et al has found no significant difference in the plasma thiol level in HP infected patients compared with controls [23]. Baykan et al reported that there was no difference between the total thiol, native thiol, disulphide/native thiol and dissulphide/total thiol ratios of the HP (+) patients and control group [24]. They claimed severity of inflammation affected their results.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study involving patients with H. pylori infection showed a correlation between the severity of endoscopically detected gastritis and the plasma disulfide level. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%